Case Report: Persistent toxic reactions in a toddler with a negative blood cantharidin toxicology test - Duan, Zhuyan; Qu, Yanning; Tang, Rui; Sheng, Mengyi; Wang, Liangliang; Li, Jiao; Zheng, Si; Guo, Linying (Frontiers in Pediatrics, 2025)
Cantharidin is a potent natural toxin and has been used in traditional Chinese medicine to treat cancers and various ailments such as rabies or psoriasis. However, improper use of cantharidin can easily lead to poisoning. Despite there is an increasing amount of literature on the toxic mechanisms of cantharidin, there is still limited knowledge about the disease progression, toxic reactions and toxic blood concentrations in children with cantharidin poisoning. Caregivers of children suffering from cantharidin poisoning might fail to provide an accurate exposure dose when the children exhibit symptoms of intoxication. Moreover, the detection results on routine blood drug screens may be negative, thus delaying the clinical diagnosis and treatment. This study describes a case of cantharidin poisoning in a 2-year-old boy who ingested a traditional Chinese herbal remedy for dog bites. The toddler exhibited severe symptoms related with digestive and urinary systems. Though cantharidin was no longer detectable in the blood 20 h after admission, the poisoning symptoms persisted for approximately 5 days, and ultrasound showed that there was still sediment in the bladder two weeks after discharge. This case highlights the need for clinicians to consider the widespread tissue distribution of cantharidin, which may lead to prolonged toxic reactions.